In vitro performances of hypocotyl and cotyledon explants of tomato cultivars under sodium chloride stress - Mohamed, Abdalmajid Nasher; Ismail, Mohd Razi; Abdul Kadir, Mihdzar; Mohd Saud, Halimi (Academic Journals, 2011)
A plant tissue culture technique is a good method for the evaluation and screening of plant genotypes for salt tolerance. In vitro evaluations of sodium chloride (NaCl) effects on two tomato cultivars (Pearl and Beril) were investigated with four NaCl levels (0, 25, 50 and 75 mM) using hypocotyl and cotyledon explants. The explants were cultured in MS media having 2.0 mg/l BAP along with different concentrations of NaCl. Sodium chloride stress negatively affected the growth traits and chlorophyll content. Significant differences were noticed between the cultivars followed by different NaCl levels, where the Beril responded superior than that of Pearl. The type of explant showed a difference in their response to shoots regeneration under NaCl stress, where the cotyledon explants achieved best results than hypocotyl explants.